(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Tracing theconflicts, the desires, the Deceitfulness and hypocrisies inherent in theuniversity set up, the thesis demonstrates that individuals within the academeare m no way different from those outside the academe. They try to put on amask that everything is fine but the writers of academic novels are engaged inthe task of tearing this mask and portraying the insider’s real experience andperception. The thesis is divided into eight chapters and the introductiongives a brief critical survey of the American academic novel and of academicnovels from various other regions of the world It tries to show the differencesin the attitude of various writers of academic novels While certain novelistsare engaged in depicting the plight of professors, some others are keen onshowing the students’ problems, yet others deal with the problems on theadministrative side But whatever may be the area of study, these writers arekeen on assessing the flaws in the University They cannot leave it, because itis the arena from which they can speak. Finally the thesis projects the viewthat though the academicians have their defects yet we should allow room forthe fact that they too are individuals and they too are liable to makemistakes. That is why writers like John Barth resort to black humor to pointout the mistakes of those within the university. Indirectly he wants reform ouruniversities and colleges and he has to a certain extent made individuals thinkabout their role in forming our universities. He has kindled us to think, butthe outcome is very difficult to assess.